Technical Feasibility and Optimization of Photovoltaic Solar Panels in the Central Area of Peru. - Melgar Dionicio, Kattia Eliana (2024)
This work evaluates the technical feasibility of installing photovoltaic solar panels for homes in the city of Huancayo, Peru. For this, variables such as: solar radiation, orientation, angle of inclination and electrical power were taken into account. The development of the study was carried out in the renewable energy laboratory of the electrical and electronic engineering faculty of the National University of Central Peru, which is located in the city of Huancayo. The prototype used was model YI6R-30P, polycrystalline silicon at 30 watts and 12 VDC. With the objective of optimizing the variables of the study for the efficient use of the solar panels that are being used in the present work. The data collection was evaluated in 3 consecutive months of this year, where the electrical power generated according to the solar radiation obtained during each month, with an orientation (0°N and 45°NE), and angle of inclination has been measured. (13th and 16th). In conclusion, the most efficient design is: 7 hours of high solar radiation, with an inclination angle of 16°, oriented towards the North-East, and electrical power of 20 watts.